Analysing the Launch of COVID-19 Vaccine National Rollouts: Nine Case Studies - John Gannon; Razieh Azari; Marta Lomazzi; Bettina Borisch (MDPI AG, 2021)
In late 2020 and early 2021, with the eagerly anticipated regulatory approval of vaccines against SARS-CoV-2, the urgent global effort to inoculate populations against this devastating virus was underway. These case studies examine the early stages of COVID-19 vaccine rollouts across nine regions from around the world (Brazil, India, Indonesia, Ireland, Israel, Nigeria, Taiwan, United Kingdom and United States). By evaluating and comparing different approaches used to immunize against a novel pathogen, it is possible to learn a great deal about which methods were successful, and in which areas strategies can be improved. This information is applicable to the ongoing global vaccination against this virus, as well as in the event of future pandemics. Research was conducted by following and tracking the progress of vaccine rollouts in the nine regions, using published clinical trials, government documents and news reports as sources of data. Results relate to the proportion of populations that had received at least one COVID-19 dose by 28 February 2021. Outcomes are discussed in the context of three key pillars integral to all immunization programs: procurement of vaccines, communication with the public and distribution of doses to individuals.